An Approach to Color Change and Quality Relation in Roughages - Ahmet İnce; Yasemin Vurarak (Journal of Agricultural Sciences)
In this work, it was aimed to associate CIELAB Scale (L*, a*, b*) with some quality parameters of roughages such as pH, crude protein (CP) and relative feed value (RFV). To this end, five different applications; haylages unwrapped on 25th, 40th and 55th days of fermentation, traditional silage unwrapped 55th days of fermentation and degraded haylage were examined for vetch-triticale (Vicia sativa L. - Triticasecale wittmack) and caramba-berseem clover (Lolium multiflorum cv Caramba-Trifolium alexandrinum L.) mixtures in the study. The tests were conducted according to randomized block design with three replications for both forage mixtures. The ΔL and Δb color values and pH, CP, RFV were significantly correlated in the vetch-triticale mixture. The regression coefficients (R2) for ΔL and Δb were 0.68 and 0.79 for pH, 0.40 and 0.38 for CP, 0.63 and 0.70 for RFV, respectively. In the mixture of the caramba - berseem clover, the regression coefficients for ΔL and Δb were found to be 0.64 and 0.85 for pH, 0.14 and 0.12 for CP, 0.28 and 0.37 for RFV respectively. In both mixtures, the level of relation between Δa* color value and quality parameters remained very low. Also, it was obtained that the best roughage in terms of RFV was haylages opened after 55th days. Decreasing the L*, b* color values by 50% on average after fermentation can be regarded as an indication of roughage degradation and RFV reduction. From this point view, it can be possible to determine the quality change by following the colors before and after fermentation of roughage.